Arabis alpina: A perennial model plant for ecological genomics and life‐history evolution. (7th September 2021) - Wötzel, Stefan; Andrello, Marco; Albani, Maria C.; Koch, Marcus A.; Coupland, George; Gugerli, Felix
Abstract: Many model organisms were chosen and achieved prominence because of an advantageous combination of their life‐history characteristics, genetic properties and also practical considerations. Discoveries made in Arabidopsis thaliana, the most renowned noncrop plant model species, have markedly stimulated studies in other species with different biology. Within the family Brassicaceae, the arctic–alpine Arabis alpina has become a model complementary to Arabidopsis thaliana to study the evolution of life‐history traits, such as perenniality, and ecological genomics in harsh environments. In this review, we provide an overview of the properties that facilitated the rapid emergence of A .  alpina as a plant model. We summarize the evolutionary history of A .  alpina, including genomic aspects, the diversification of its mating system and demographic properties, and we discuss recent progress in the molecular dissection of developmental traits that are related to its perennial life history and environmental adaptation. From this published knowledge, we derive open questions that might inspire future research in A .  alpina, other Brassicaceae species or more distantly related plant families.